The Importance of Teaching Electromagnetic Radiation Interaction in High Schools - Kotsis, K. T. (Universitas Negeri Yogyakarta, 2024)
The advantages of including electromagnetic radiation interaction in the high school curriculum are thoroughly analyzed in this work. The possible effects on students' knowledge of fundamental physics ideas and their capacity to apply these ideas in practical situations are investigated in this study. The study underlines the need to arm pupils with a thorough knowledge of electromagnetic radiation by analyzing the present educational scene and high school science teachers' difficulties. The methods used in this paper include a critical review of the literature with a qualitative approach, an examination of educational impacts, a discussion of practical applications, an analysis of future implications, and educational recommendations. Moreover, the conversation will cover the possible consequences for academic interests and future professional paths for students with a strong background in this field. Using critical analysis of current literature and instructional strategies, this paper seeks to promote a more solid way to teach electromagnetic radiation interaction at the high school level. Therefore, the article will lead readers through a rational sequence of ideas and data to support this significant educational project.